Pemilihan Presiden dalam Islam - Agus Nugraha (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2004)
Indonesia, with the largest Muslim population in the world, for the first time in 2004 conducted direct presidential elections. This certainly will serve as a reference for other Muslim nations in selecting their leaders. Islam, as the religion embraced by the majority of the Indonesian people, has undergone a long historical journey in choosing the country’s leaders or president. As a reference point, one can examine the practices of leadership selection during the era of the Rightly Guided Caliphs (Khulafa’ Al-Rasyidin), and subsequent Islamic governance. Moreover, although the Qur’an and Sunnah do not explicitly provide a pattern for selecting leaders, Islamic thinkers have offered concepts on how the Muslim community should choose its president. The results of this study indicate that generally there are three patterns of selecting a president in Islam: the appointment pattern, the consultation pattern involving representatives of the people, and the pattern of direct election by the people.